2017
DOI: 10.1186/s13613-017-0243-z
|View full text |Cite
|
Sign up to set email alerts
|

Patient-important outcomes in randomized controlled trials in critically ill patients: a systematic review

Abstract: BackgroundIntensivists’ clinical decision making pursues two main goals for patients: to decrease mortality and to improve quality of life and functional status in survivors. Patient-important outcomes are gaining wide acceptance in most fields of clinical research. We sought to systematically review how well patient-important outcomes are reported in published randomized controlled trials (RCTs) in critically ill patients.MethodsLiterature search was conducted to identify eligible trials indexed from January … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
109
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(113 citation statements)
references
References 51 publications
1
109
1
2
Order By: Relevance
“…For all 1205 patients, the median duration of mechanical ventilation was 16 days (IQR 10-27) and that of ICU length of stay 22 days (IQR 14-36). The median duration of ventilation (20 days [IQR [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] vs. 11 days [IQR 6-16], p < 0.001) and ICU stay (p < 0.001, Table 1) was twice as long for tracheotomised patients. Primary 877 ARDS patients survived and discharged from ICU.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For all 1205 patients, the median duration of mechanical ventilation was 16 days (IQR 10-27) and that of ICU length of stay 22 days (IQR 14-36). The median duration of ventilation (20 days [IQR [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] vs. 11 days [IQR 6-16], p < 0.001) and ICU stay (p < 0.001, Table 1) was twice as long for tracheotomised patients. Primary 877 ARDS patients survived and discharged from ICU.…”
Section: Resultsmentioning
confidence: 99%
“…A current systematic review of patient-important outcomes for critically ill patients in randomised controlled clinical studies has shown ICU mortality to be the most frequently measured clinical outcome. Only 10% of studies have included at least one patient-important outcome in addition to mortality after ICU discharge [26]. It should be noted that, in contrast to mortality, HRQoL is a complex construct that contains individual aspects with multiple dimensions, often operationalised as social, somatic and psychological variables [4].…”
Section: Discussionmentioning
confidence: 99%
“…Outcomes preferred by investigators may not be what is important to patients. Trials involving critically ill patients rarely measure patient-reported outcomes as the primary or secondary outcome measure (5 vs. 22%, respectively) [96]. Patients and their family members involved in the Core Outcomes Set for Cardiac Arrest (COSCA) process identified survival, neurological function and HRQoL as the preferred outcome measures [97].…”
Section: Future Directionsmentioning
confidence: 99%
“…However, guidelines have traditionally focused on early recognition and management, not mitigation of longer-term sequelae 19 . Likewise, clinical trials typically use shorter-term mortality endpoints and only rarely collect data on functional outcomes or quality of life 20,21 . Perhaps not surprisingly given the lack of attention to sepsis survivorship, many patients report dissatisfaction with follow-up care after hospitalization 22 .…”
Section: Introductionmentioning
confidence: 99%